Influence of CT utilisation on patient flow in the emergency department: a retrospective 1-year cohort study. Issue 5 (4th May 2016) - Li, Chao-Jui; Syue, Yuan-Jhen; Lin, Yan-Ren; Cheng, Hsien-Hung; Cheng, Fu-Jen; Tsai, Tsung-Cheng; Chen, Kuan-Fu; Lee, Chien-Hung
Abstract : Objective: CT, an important diagnostic tool in the emergency department (ED), might increase the ED length of stay (LOS). Considering the issue of ED overcrowding, it is important to evaluate whether CT use delays or facilitates patient disposition in the ED. Design: A retrospective 1-year cohort study. Setting: 5 EDs within the same healthcare system dispersed nationwide in Taiwan. Participants: All adult non-trauma patients who visited the 5 EDs from 1 July 2011 to 30 June 2012. Interventions: Patients were grouped by whether or not they underwent a CT scan (CT and non-CT groups, respectively). Primary and secondary outcome measures: The ED LOS and hospital LOS between patients who had and had not undergone CT scans were compared by stratifying different dispositions and diagnoses. Results: CT use prolonged patient ED LOS among those who were directly discharged from the ED. Among patients admitted to the observation unit and then discharged, patients diagnosed with nervous system disease had shorter ED LOS if they underwent a CT scan. CT use facilitated patient admission to the general ward. CT use also accelerated patients' admission to the intensive care unit (ICU) for patients with nervous system disease, neoplasm and digestive disease. Finally, patients admitted to the general wards had shorter hospital LOS if they underwent CT scans in the ED. Conclusions: CT use did not seem to have delayed patient disposition in ED. While CT use facilitated patient disposition if they were finally hospitalised, it mildly prolonged ED LOS in cases of patients discharged from the ED.